Determining the Value Hierarchies of the 'Z' Generation - Sevda Ceylan-Dadakoğlu; Atilla Özdemir; Baran Dadakoğlu (Istanbul Kültür University, 2023)
This study aims to determine the value hierarchies of Z-generation students. The research was carried out in Ankara in November and December of 2021. The Rokeach Values Inventory was used to reveal the value rankings of the students, and 985 students studying at a public high school were reached within the scope of the research. The research was carried out using the cross-sectional survey model, one of the quantitative research methods. Obtained data were analyzed with the Mann-Whitney U test and Kruskal-Wallis H test. According to the analysis results, it was seen that the "Z" generation attaches the most importance to freedom, family security, afterlife security, happiness, and comfortable life, among the terminal values. It was observed that students preferred to be independent, honest, logical, courageous, and intellectual the most, respectively, among instrumental values.